Constructive solutions for energy saving in buildings - Sakhaeva A.K. Сахаева А.Қ.; Seidemetov B.M. Сеидеметов Б.М. (Рroblems of engineering and professional education, 2023)
In this article, structural systems, construction materials, equipment and products in development, the requirements of energy saving and environmental safety, labor costs less than spending, the economy in modernization and reconstruction of residential and industrial buildings in accordance with the requirements outlined in the development of traditional and new methods. The main factors with regard to the requirements of energy saving and instructions noted. In this regard, the use of construction products and modernization of buildings, the use of energy-saving and spaceplanning decisions, is a key factor in building waste less heat loss is characterized by appear.